Biodegradability determination of municipal waste: an evaluation of methods - Godley, Andrew R.; Lewin, Kathy; Graham, Adele; Barker, H.; Smith, Richard (The Waste Conference Limited, 2004)
The Environment Agency is required to monitor the diversion of biodegradable municipal waste (BMW) from landfill. Reliable methods are needed to measure the biodegradability of municipal waste, both as mixed municipal waste and as individually separated fractions. An evaluation of several methods was carried out using a variety of organic materials typically found in municipal solid waste. The assessment considered biological and non-biological methods to determine which provides the bestfit surrogate measurement for relative waste biodegradability. The biological methods tested were: the aerobic specific oxygen uptake rate, dynamic respiration index tests, and the anaerobic biochemical methane potential test. The non-biological methods evaluated were: dry matter, loss on ignition, total organic carbon, total nitrogen, water extractable dissolved organic carbon, biological oxygen demand, chemical oxygen demand, lignin and cellulose content and cellulase hydrolysis. This paper also reviews how such tests can be used to measure the relative biodegradation of municipal waste and benchmark the relative diversion from landfill achieved by the pre-treatment of municipal waste in a mechanical biological treatment (MBT) process.